COMPARING SNOWBALL THROWING TECHNIQUE WITH SCIENTIFIC APPROACH IN IMPROVING SPEAKING SKILL - Bestari Retno Wardani; Aulia Rachman; Intan Satriani (IKIP Siliwangi, 2019)
This research purpose is to analyse the capability of students’ speaking improvement through Snowball Throwing Technique. The research method applied in this research is quantitative method with a quasi-experimental design. This research had been conducted at SMP Wiyata Bakti Cimahi. The sample for this research took 30 students from each class, that is class 8C selected become the experiment class that used Snowball Throwing Technique and class 8A selected become the control class that used the Scientific Approach. The research result concluded that: (1) the students’ speaking capability through Snowball Throwing Technique is better than Scientific Approach and (2) the students’ speaking capability improvement through Snowball Throwing Technique is better than Scientific Approach.Keywords: Speaking, Snowball Throwing Technique, Scientific Approach, Quasi-experiment